Where are the limits of the effects of exercise intensity on cognitive control? - Karen Davranche; Jeanick Brisswalter; Rémi Radel (Elsevier, 2015)
Purpose: This study aimed to investigate whether workload intensity modulates exercise-induced effect on reaction time (RT) performances, and more specifically to clarify whether cognitive control that plays a crucial role in rapid decision making is altered. Methods: Fourteen participants performed a Simon Task while cycling 20 min at a light (first ventilatory threshold, VT1 - 20%), moderate (VT1), or very hard (VT1 + 20%) level of exercise. Results: After 15 min of cycling, RTs are faster than during the first 5 min of exercise. This benefit does not fluctuate with the intensity of exercise and enlarges as RT lengthens. Despite a numerical difference suggesting a greater facilitation during moderate exercise (−16 ms) than during a light exercise (−10 ms), the benefit is not statistically different. Interestingly, we did not observe any signs of worsening on RT or on accuracy during very hard exercise. Conclusion: Cognitive control is extremely robust and appears not to be affected by the intensity of exercise. The selective inhibition and the between-trials adjustments are effective from the beginning to the end of exercise, regardless of the workload output.